Digital image correlation: a technique for determining local mechanical conditions within early bone callus. - Thompson, M; Schell, H; Lienau, J; Duda, G (2007)
Local mechanical conditions are known to play a role during the regeneration of musculoskeletal tissues, and histomorphometrical investigations of the time course of healing have enabled specific conclusions regarding the mechanosensitivity of tissue differentiation. However, the mechanism for this influence is not clearly understood. In order to extend this analysis, it is essential to link local histological understanding with direct characterisation of the local mechanical environment. Digital image correlation (DIC) is a computer-based image analysis technique that enables the non-contact measurement of strains on material surfaces and is finding application in many areas of biomechanics. Here we report a DIC technique to investigate the local distribution of mechanical strain within regenerating soft tissue sections. We provide exemplary data from analysis of a section of sheep bone callus. An assessment of displacement measurement accuracy gave an RMS error of 4.2 microm, corresponding to an estimated strain error of 1.4%. The sections showed concentrations of up to four times the applied strain and comparison of the strain patterns with histological analysis confirmed that these concentrations reflected boundaries between hard and soft callus.